Immune responses in children with secondary infection of mycoplasma pneumoniae after COVID-19: focus on eosinophils and IgE - Pingping Wang; Jin Yao; Yaqiong Li; Zhanjun Zhang; Ruiling Zhang; Shouting Lu; Meixia Sun; Xiaorong Huang (BMC Infectious Diseases)
Abstract Background The COVID-19 (SARS-CoV-2) epidemic has posed a major challenge to global public health, especially in children. Some children may experience secondary infection with Mycoplasma pneumoniae after SARS-CoV-2 infection, which has attracted widespread attention. Studies have shown that eosinophils play an important role in respiratory tract infections and are involved in regulating immune responses and inflammatory processes. However, there is a lack of systematic research on the specific manifestations and mechanisms of eosinophils in secondary infection with Mycoplasma pneumoniae after SARS-CoV-2 infection. Objective This study aims to explore the characteristics of immune response in children with SARS-CoV-2 infection and Mycoplasma pneumoniae infection, focusing on the changes in immune indicators such as eosinophils (EOS), immunoglobulin E (IgE), interleukin-6 (IL-6), C-reactive protein (CRP), and procalcitonin (PCT). Methods This study is a retrospective observational study, and a total of pediatric patients who were treated in our hospital from January 2023 to December 2023 were included. The study group included children who were diagnosed with SARS-CoV-2 infection and further infected with Mycoplasma pneumoniae, and the control group included children who were only infected with SARS-CoV-2 and had no other pathogens. The clinical data of the two groups of patients, including absolute eosinophil value, IgE quantification, IL-6, CRP and PCT levels, were collected and analyzed, and statistical comparisons were performed. Results A total of 134 children were included, including 79 in the study group and 55 in the control group. The absolute eosinophil value [0.17 (0.09, 0.31) vs. 0.09 (0.06, 0.23), P < 0.01] and IgE level [59.28 (37.54, 256.88) vs. 22.00 (11.00, 113.10) P < 0.01] of the children in the study group were significantly higher than those in the control group, while IL-6 [16.81(4.72,31.86) vs. 9.5(3,57.3), P = 0.602], CRP [2.82(1.10,6.13) vs. 1.94(0.50,8.94), P = 0.528] and PCT[0.12(0.08,0.20) vs. 0.12(0.10,0.24), P = 0.329] were no significant difference between the two groups. Binary logistic regression analysis showed that the absolute value of eosinophils and IgE were independent risk factors for secondary infection of Mycoplasma pneumoniae after SARS-CoV-2 infection. Conclusion This study shows that after SARS-CoV-2 infection, the increase in eosinophils and the increase in related immune indicators IgE may be closely related to secondary infection with Mycoplasma pneumoniae. This study provides an important basis for understanding the immune response of children after SARS-CoV-2 infection and its related clinical management, suggesting that clinicians should closely monitor the eosinophil count and IgE level of children after SARS-CoV-2 infection, especially for children at risk of secondary infection, so as to take timely intervention measures to prevent secondary infection with Mycoplasma pneumoniae and improve the prognosis of children.